Peningkatan Pengetahuan Melalui Edukasi Bahaya Merokok Pada Siswa-Siswi SMP N 27 Padang - Elsa Marsellinda; Rizki Yulion Putra; Mexsi Mutia Rissa (STIKes Ibnu Sina Ajibarang, 2024)
The prevalence of active smokers in Indonesia continues to increase. Efforts to prevent smoking behavior in adolescence are very important to reduce long-term health risks. The purpose of this community service is to increase knowledge about the dangers of smoking. This community service was given to 50 students with counseling using leaflets and power points. In general, the implementation of this community service was categorized as successful and went well. There was an increase in knowledge about the content of cigarettes and the dangers of smoking after counseling.